JURIDICAL ANALYSIS OF BUSINESS CONVENIENCE FOR MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN MEDAN CITY - Faris Bashel, Yasmin; Saidin, Saidin; Ikhsan, Edy; Devi Azwar, T.Keizerina (RADJA PUBLIKA, 2022)
The problems faced by MSME business actors are licensing and capital issues to continue their business in the midst of the COVID-19 pandemic. So special attention is needed for MSME actors from the Government during a pandemic. This research uses normative legal research and empirical legal research. Therefore, the data used include primary data and secondary data. Data were collected using library research and field research using interview methods. The results of the study indicate that the ease of doing business permits for MSME business actors according to the job creation law will be freed from business licensing fees and will provide cost relief for small businesses. The Government's policy is to provide social assistance to MSMEs affected by COVID-19 in the amount of 2.4 million Rupiah. Obstacles Faced First, there are obstacles in terms of licensing, the second is obstacles in distributing BPUM, and the third is the obstacles to providing capital credit for Micro, Small and Medium Enterprises (MSMEs).